Revisiting the Mechanism Behind Transition-Metal Dissolution from Delithiated LiNixMnyCozO2 (NMC) Cathodes. Issue 2 (16th January 2020) - Sahore, Ritu; O'Hanlon, Daniel C.; Tornheim, Adam; Lee, Chang-Wook; Garcia, Juan C.; Iddir, Hakim; Balasubramanian, Mahalingam; Bloom, Ira
Abstract : Dissolution of transition metals (TMs) from lithium-ion battery cathodes under high-voltage conditions is a major issue affecting battery performance that is not well understood mechanistically. Here, this phenomenon is studied by chemically aging pristine and charged LiNi0.5 Mn0.3 Co0.2 O2 (NMC532) cathodes in the presence of different solutions. The solution composition was varied by 1) adding water to a standard electrolyte, 2) replacing LiPF6 salt with lithium acetylacetonate (Li-acac), 3) and/or adding oxidatively unstable tris(2, 2, 2-trifluoroethyl) phosphite (TTFP) as an electrolyte additive. Our results demonstrate that while TM dissolution from pristine NMC532 cathodes is dominated by HF-attack, TM dissolution from charged NMC532 cathodes is affected by many other factors apart from HF-attack. We suggest that reduction of TMs due to chemical/electrochemical oxidation of the electrolyte at cathode/electrolyte interface, followed by formation of soluble TM-complexes with concomitant Li + intercalation into the cathode, is the dominant mechanism of TM-dissolution at high voltage.